Trends, challenges and opportunities for MOOCs in learning mathematics: a bibliometric analysis - Tomi Listiawan; Juharyanto Juharyanto; Rochmawati Rochmawati; Angga Yuni Mantara; Djatmiko Djatmiko (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2025)
This study examines the trends, challenges, and opportunities in the use of Massive Open Online Courses (MOOCs) within mathematics education. Employing a descriptive bibliometric approach, this research analyzed 1.800 publications indexed in Dimensions.ai from 2020 to 2025 using VOSviewer software to visualize and interpret keyword co-occurrence, citation patterns, and research networks. The results indicate a substantial growth in MOOC related mathematics studies from 2020 to 2022, followed by stabilization during 2023–2025, signaling the transition of MOOCs from emergency digital instruction toward a more structured and sustainable learning ecosystem. The visualization results identified four dominant thematic clusters: (1) pedagogical engagement and learning design, (2) data analytics and intelligent systems, (3) access, equity, and institutional policy, and (4) cognitive and affective learning outcomes. Despite significant progress in expanding global access to mathematical learning, persistent challenges remain particularly low course completion rates, limited adaptivity of mathematical content, and infrastructural disparities across regions. Nevertheless, the integration of AI-based personalization, learning analytics, and immersive technologies (VR/AR) provides promising directions for enhancing mathematical reasoning, engagement, and teacher professional development. Overall, this study contributes a comprehensive bibliometric overview and highlights the potential for MOOCs to evolve into adaptive, equitable, and data-informed digital learning ecosystems that advance the quality and inclusivity of mathematics education.